The Role of the Organic Moiety in the Diffusion and Transport of Carboxylates into Liposomes - Aaron Torres-Huerta; Hennie Valkenier (Molecules)
Understanding carboxylate transport through lipid membranes under physiological conditions is critical in biomedicine and biotechnology, as it allows for the emulation of biological membrane functions and can enhance the absorption of hydrophobic carboxylate-based drugs. However, the structural diversity of carboxylates has made it challenging to study their transport, and the limited available examples do not provide a comprehensive understanding of the role of the organic moiety in this process. Here, we present an in-depth analysis of the diffusion and transport of various aliphatic and aromatic carboxylates into liposomes. We assessed the influence of their size, number of carboxylate groups, and presence of hydroxyl groups. Our findings from fluorescence assays, using lucigenin and HPTS as probes, revealed that most carboxylates can spontaneously diffuse into liposomes in their protonated state, facilitated by the efflux of HNO3 when using NaNO3 solutions at pH 7. The Cl-ISE assay showed chloride/carboxylate exchange by a synthetic anion transporter. Clear trends were observed when the organic moiety was systematically varied, with a particular enhancement of anion transport by the presence of hydroxyl groups in the aromatic carboxylates. Our findings provide insights into the processes by which carboxylates can enter liposomes, which can contribute to understanding the transport of other biologically relevant organic anions.